The Preventive Effect of Curcumin on the Experimental Rat Epidural Fibrosis Model - Demirel, Cem; Turkoz, Dursun; Yazicioglu, Irem Melike; Cokluk, Cengiz (Elsevier Science Inc, 2021)
OBJECTIVE: The aim of the study was to evaluate the effect of systemically administrated curcumin on the prevention of peridural fibrotic tissue and adhesion formation in a rat laminectomy model. METHODS: Thirty-two Wistar albino rats were randomly selected and equally divided into 4 groups as follows: negative control group (group I) did not undergo operation; positive control group (group II) underwent laminectomy without treatment; group III (low-dose curcumin; 100 mg/kg); and group IV (high-dose curcumin; 200 mg/kg). Curcumin was administered intraperitoneally per day for 7 days after surgery starting from day 0. Twenty-eight days after surgery, T12 and 14 vertebral columns, paraspinal tissues, and epidural scar tissue were dissected en bloc and prepared for histopathologic examinations. All specimens were examined for inflammation, epidural fibrosis (EF), foreign body reaction, medulla spinalis retraction, granulation tissue, and arachnoid involvement. A Kruskal-Wallis test followed by a Dunn multiple comparison test were used for statistical analysis, and a P value <0.05 was considered as statistically significant. RESULTS: Curcumin treatment significantly reduced inflammation, foreign body reaction, granulation tissue formation, medulla spinalis retraction, and EF formation compared with positive control group (P < 0.05); however, no significant differences were found between the 2 groups that received different doses of curcumin. CONCLUSIONS: The results of the present study showed that systemic administration of curcumin was effective in reducing EF formation, inflammation, granulation tissue formation, medulla spinalis retraction, and foreign body reaction in the laminectomy area. Our results suggest that antiinflammatory activities of curcumin are beneficial for attenuation of EF formation.
Yazicioglu, Irem Melike/0000-0002-8190-6722; Demi̇rel, Cem/0000-0002-6084-4075;
Keywords: Curcumin; Epidural Fibrosis; Granulation; Inflammation; Laminectomy